Linking Evangelical Subculture and Phallically Insecure Masculinity Using Google Searches for Male Enhancement - Perry, Samuel L. (Journal for the scientific study of religion, 2021)
Numerous studies document the connection between American evangelicalism and male insecurity stemming from essentialist, phallocentric conceptions of masculinity. Yet data have often been confined to individuals’ responses in surveys or qualitative interviews. This limits our understanding because individuals may lie about the most personal sources of insecurity (even to themselves) and such data are difficult to aggregate to broader subcultural influences. Building on a moral communities’ framework, in this research note we analyze Google Trends data and focus on the prevalence of explicit searches for “male enhancement” terms and phrases, simultaneously indicating (1) the internalization of a subculture that prioritizes essentialist, phallocentric standards of masculinity and (2) a privately felt failure to meet those standards. Even after accounting for a host of state-level confounds, the preponderance of evangelicals in a state consistently predicts more Google searches for terms and phrases like “male enhancement,” “ExtenZe,” “penis pump,” “penis enlargement,” and others. We theorize that the largely patriarchal―and increasingly embattled and radicalized―evangelical subculture explicitly or implicitly promotes equating masculinity with physical strength and size, leaving men influenced by that subculture (whether evangelical or not) to seek solutions for their privately felt failure to measure up.